MODERN INFORMATION TECHNOLOGIES AND COMPUTER DIAGNOSTICS OF DEVELOPMENT OF COMMUNICATIVE CULTURE OF THE TEACHER (Journal of Information Technologies in Education (ITE), 2009)
This article is devoted to express train – diagnostics of a level of development of communicative culture of the teacher with the help of computer testing and analysis of the computer program of testing basing on criterial model of appraisement of communicative qualities of the teacher.
Keywords: information technologies; communicative culture; computer testing